Archaeology as Political Action. - McGuire, Randall H. (California series in public anthropology., 2004)
Develops a theory and framework to describe how archaeology can contribute to a more humane world. Recognizing that archaeology is an inherently political activity, this book builds on the history of archaeological theory and Marxist dialectical theory to point out how archaeologists can use their craft to evaluate interpretations of this world.